Survival rates of short (6 mm) micro‐rough surface implants: a review of literature and meta‐analysis. Issue 5 (18th February 2013) - Srinivasan, Murali; Vazquez, Lydia; Rieder, Philippe; Moraguez, Osvaldo; Bernard, Jean‐Pierre; Belser, Urs C.
Abstract Objective The aim of this review was to test the hypothesis that 6 mm micro‐rough short Straumann® implants provide predictable survival rates and verify that most failures occurring are early failures. Materials and methods A PubMed and hand search was performed to identify studies involving micro‐rough 6‐mm‐short implants published between January 1987 and August 2011. Studies were included that (i) involve Straumann® 6 mm implants placed in the human jaws, (ii) provide data on the survival rate, (iii) mention the time of failure, and (iv) report a minimum follow‐up period of 12 months following placement. A meta‐analysis was performed on the extracted data. Results From a total of 842 publications that were screened, 12 methodologically sound articles qualified to be included for the statistical evaluation based on our inclusion criteria. A total of 690 Straumann® 6‐mm‐short implants were evaluated in the reviewed studies (Total: placed‐690, failed‐25; maxilla: placed‐266, failed‐14; mandible: placed‐364, failed‐5; follow‐up period: 1–8 years). A meta‐analysis was performed on the calculated early cumulative survival rates (CSR%). The pooled early CSR% calculated in this meta‐analysis was 93.7%, whereas the overall survival rates in the maxilla and mandible were 94.7% and 98.6% respectively. Implant failures observed were predominantly early failures (76%). Conclusion This meta‐analysis provides robust evidence that micro‐rough 6‐mm‐short dental implants are a predictable treatment option, providing favorable survival rates. The failures encountered with 6‐mm‐short implants were predominantly early and their survival in the mandible was slightly superior.